Thomas M. Osborne Jr, Human Action in Thomas Aquinas, John Duns Sco- tus & William of Ockham, Washington DC: The Catholic University of America Press 2014, ss. XXV+250. - Niewiadomski, Krzysztof (Teologia i Moralność, 2018)
Thomas M. Osborne Jr, Human Action in Thomas Aquinas, John Duns Sco- tus & William of Ockham, Washington